ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH COVID 19 PADA PERUSAHAAN MANUFAKTUR SUB OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI - Andri Andri; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The purpose of this study was to determine the financial performance before and after Covid-19 in sub-automotive and component manufacturing companies listed on the Indonesian Stock Exchange. The financial ratios used are the Current Ratio, Debt to equity Ratio, Return on Assets, and total asset turnover. the type of data used is quantitative data obtained from the Indonesia Stock Exchange. Sampling was carried out using purposive sampling method in order to obtain 12 companies as a sample of 14 companies listed on the IDX. The data analysis method used in this study was descriptive analysis using the different test method using the paired sample t-test and the Wilcoxon sign rank test to determine the hypothesis that was previously tested for normality. The results of data analysis show that liquidity, solvency, profitability and activity in automotive and component companies listed on the IDX had differences before and after Covid-19.